If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16(x + 6) = 2(x + -14) Reorder the terms: -16(6 + x) = 2(x + -14) (6 * -16 + x * -16) = 2(x + -14) (-96 + -16x) = 2(x + -14) Reorder the terms: -96 + -16x = 2(-14 + x) -96 + -16x = (-14 * 2 + x * 2) -96 + -16x = (-28 + 2x) Solving -96 + -16x = -28 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -96 + -16x + -2x = -28 + 2x + -2x Combine like terms: -16x + -2x = -18x -96 + -18x = -28 + 2x + -2x Combine like terms: 2x + -2x = 0 -96 + -18x = -28 + 0 -96 + -18x = -28 Add '96' to each side of the equation. -96 + 96 + -18x = -28 + 96 Combine like terms: -96 + 96 = 0 0 + -18x = -28 + 96 -18x = -28 + 96 Combine like terms: -28 + 96 = 68 -18x = 68 Divide each side by '-18'. x = -3.777777778 Simplifying x = -3.777777778
| 3z+1=-z-2 | | 2q+5q-2=180 | | 6[3-(-5x-4)]=240x+210 | | 2q+5-2=180 | | 2-2/3x=-1/2 | | 9x+6y=93.9 | | 3-x^2=33-3x^2 | | 9w+99+w+71=180 | | 2-4/6x=-1/2 | | kx^2-3x+25=0 | | -u+216=174 | | 1/3m=-8 | | (8t-3)=3(t+1)+3 | | -2p-0.5p=6.875 | | 178=9-x | | (8t-3)=3(t-1) | | 134=197-w | | 6-6z=36 | | 2x+7=3y+17 | | 10x-4=5x-2 | | 8+8(X-1)=8-7(X-2) | | 9=-3.5x+1.75-1.5 | | 18x-3+4y+12= | | x(x+4)-10(x+4)=0 | | 30r+35y=950 | | -7w+6w+4=-8 | | 4(-2+5)=12 | | 5p+7-4p=-7 | | .2m-.8m-7=5.12 | | 22m+6n+4m-8= | | 2x/x-35 | | y-12-4=-5 |